Dia dos Avós - Castedo, Isabel Aparecida; Roman, Cíntia Terezinha da Cunha; Assis, Edilene Batista de; Lima, Sara Santos; Moura, Zuellen Santos de; Guimarães, Renata Maria de Sousa; Lopes, Cleuza Francisca da Silva; Lima, Maria dos Santos; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf